Codon Optimization and Epitope Identification of L1 Protein Human Papillomavirus Type 52 for Expression in Lactococcus lactis: Codon Optimization and Epitope Identification L1 Protein HPV52 - Prastyowati, Anika; Hakim, Mohamad Saifudin; Wijayanti, Nastiti; Wibawa, Tri (Journal of Tropical Life Science, 2026)
Human papillomavirus (HPV) type 52 is among the top three high-risk oncogenic types that are associated with cervical cancer worldwide, especially in Indonesia. Designing a vaccine against HPV using an Lactococcus lactis expression system is a promising strategy, as this bacterium is well-known for its probiotic properties and can be safely utilized as a delivery carrier for oral vaccines. This study aimed to optimize the codon usage of the L1 protein of HPV type 52 for expression in L. lactis expression system and to identify potential epitopes using bioinformatics tools. To determine the codon optimization, the L1 protein sequence of HPV type 52 was retrieved from the National Center for Biotechnology Information (NCBI) database. Furthermore, codon optimization was conducted once the model had been established using OPTIMIZER, Clustal Omega, Restriction Mapper, and the ExPASy tool, based on L. lactis. The final construct was predicted to have a B-cell epitope by Ellipro tools, antigenicity by VaxiJen v.2.0, allergenicity by AllerTOP v.2.0, and toxicity by ToxIBTL. This resulted in a potential vaccine candidate with a Codon Adaptation Index (CAI) of 0.754 and GC content of 39.0%. Identification of epitopes from the optimized gene resulted in two peptide sequences, WRPSEATVYLPPVPVSKVVS and GTLGDPVPGDLYIKGSNSGNTATVQ, as components of the vaccine candidate.